PENGEMBANGAN BAHAN AJAR PENDUKUNG DALAM BENTUK KOMIK UNTUK SISWA SMP KELAS VII PADA MATERI UNSUR, SENYAWA, DAN CAMPURAN - Neli Nilawati; Maria Paristiowati; Darsef Darwis (LPPM Universitas Negeri Jakarta, 2013)
This study aims to generate and test the feasibility of supporting teaching materials in the form of comics for junior high school students on elements, compounds and mixture subject. The study was conducted in September 2011 - May 2012 at Junior High School 47 and 148 Jakarta. It used a method of research and development which consists of three phases, namely requirements analysis phase, the stage of product development and product testing phase. Based on the analysis of the needs of students as much as 97.14% of respondents support the development of supporting materials in the form of comics, and 82.86% of respondents expressed interest in learning science students with the comic. The results of product trials to matter experts, linguists, media experts and pilot testing of products to students and teachers in small and large scale show that the interpretation for the comic value of learning that has made presentations range 72.9% - 90% so that these materials have been both viable and can be used as support materials for teaching science to the material elements, compounds and mixtures. Keywords: Teaching Material Support, Comics Learning, Methods of Research and Development